Northern Bobwhite Survival Related to Movement on a Reclaimed Surface Coal Mine - Ashley M. Unger; Evan P. Tanner; Craig A. Harper; Patrick D. Keyser; John J. Morgan (National Quail Symposium Proceedings, 2017)
Reclaimed coal mines represent opportunity to provide large tracts of early succession habitat essential to northern bobwhite (Colinus virginianus) populations. However, little research has been conducted to explore the potential of reclaimed mine sites and examine bobwhite ecology on these unique areas. Reclaimed mines in Kentucky were planted to non-native species, such as sericea lespedeza (Lespedeza cuneata) and tall fescue (Festuca arundinacea), which do not provide suitable structure for northern bobwhite brood-rearing and movement. Fallow disking (in blocks and linear firebreaks) and planting food plots are part of current management efforts to improve food availability and habitat structure for broods. We trapped and radiomarked 266 northern bobwhites between April 2010 and September 2011 on Peabody Wildlife Management Area, a 3,330-ha reclaimed coal mine in western Kentucky, USA to investigate the effects of current management practices on movement and survival. We calculated seasonal daily movement as the Euclidean distance from a location on day 1 to day 2. Breeding season (1 Apr-30 Sep) movement averaged 128 m in 2010 and 147 m in 2011. Daily movement averaged 163 m during the 2010–2011 non-breeding (1 Oct-31 Mar) season. Multiple regression analysis indicated annual food plots, disk blocks, firebreaks, and roads did not explain variation within daily movement regardless of season (R2 0.04). Individual bird/covey, precipitation, hours between locations, and average temperature also poorly explained movement variation. We used Program MARK to model the effect of season, year, mean daily movement, mean distance to annual food plots, disk blocks, firebreaks, and roads on survival. The season (breeding/non-breeding) model explained 81% of the variation in survival, and the year model explained 13%, suggesting management was not driving survival. We do not believe disking should be discontinued, although it did not influence movement, as it can improve vegetation structure important to nest-site selection and broods.
Keywords: Colinus virginianus; disking; firebreaks; Kentucky; movement; northern bobwhite; reclaimed mined land; survival; telemetry